Understanding the Psychology Behind Consumer Behavior - Dirwan, Dirwan; Latief, Fitriani (Advances in Business & Industrial Marketing Research, 2023)
Purpose: This study aims to understand the psychology behind consumer behavior by exploring the psychological, social, and emotional factors influencing individuals' purchasing decisions and consumption patterns. Research Design and Methodology: The research employs a comprehensive qualitative literature review methodology, examining academic articles, books, and other scholarly sources through systematic searches of databases such as PubMed, PsycINFO, and Google Scholar. The literature is critically reviewed and analyzed to identify key themes, theories, and findings relevant to understanding the psychology behind consumer behavior. Findings and Discussion: The findings reveal that consumer behavior is influenced by psychological processes, such as the theory of planned behavior and the elaboration likelihood model, as well as affective and social factors, including social identity theory and reference group theory. Emotional factors also play a crucial role in shaping consumer preferences and purchase decisions, with positive emotions enhancing purchase intentions and post-purchase experiences. Implications: A deep understanding of the psychology behind consumer behavior enables marketers to design more effective marketing strategies, such as emotionally resonant communication, leveraging social influence, and interventions to mitigate cognitive biases. This research provides valuable theoretical insights and practical applications for marketing strategies and consumer welfare.